TEKNIK PROGRESSIVE MUSCLE RELAXATION MEMPENGARUHI KADAR GLUKOSA DARAH PENDERITA DIABETES MELITUS TIPE 2 - Puji Astuti (Jurnal Ilmiah Kesehatan, 2014)
The high uncontrolled blood glucose level in people with Diabetes Mellitus (DM) is still often found that is resulted from the factor of psychological stress. One of the interventions to help normalize the blood glucose level is progresive muscle relaxation (PMR). Therefore, this research was purposed to find out the effect of PMR towards blood glucose level in patients with DM type 2 (DMT2). This research was pre-experimental done by applying one group pretest posttest design. The population involved all patients with DMT2 without complications hospitalized in Surabaya Islamic General Hospital, in which 22 respondents were taken as the samples by using simple random sampling technique. The independent variable was PMR, whereas the dependent one was blood glucose level. The instrument used to measure blood glucose level was a glucometer. Moreover, the data were analyzed by using paired T-test with the significance level of α = 0.05. The result of research showed that before receiving PMR, the average blood glucose level was 238.40 mg/dl, whereas before receiving PMR, the average blood glucose level was 125.68 mg/dl. Moreover, the result of Paired T-test showed that p = 0.000 < 0.05 so that H0 was rejected, illustrating that there was an effect of PMR toward blood glucose level before and after receiving PMR Discussion: In conclusion, PMR could decrease blood glucose level Therefore, the nurses in hospital should be able to do PMR done at home to balance blood glucose level in patients with DMT2 so that they can be more relaxed and independent.